Application of Democratic Leadership Style in Improving Employee Work Discipline and Motivation - Syamsidar Syamsidar; Bukman Lian; Yessi Fitriani (Yayasan Darussalam Bengkulu, 2021)
This study aims to determine whether a democratic leadership style can improve discipline and work motivation of the employees of the South OKU District education office.This study uses a qualitative approach, where the focus of this research is the education office employees of South OKU Regency with a population of 80 employees, both civil servants and honorary staff. The data analysis used in this research is analysis: 1) domain analysis; 2) taxonomic analysis; 3) comparative analysis, and 4) analysis of cultural themes.The conclusions can be drawn; 1) during his tenure the head of the South OKU District, education office has implemented a democratic leadership style, 2) this leadership style can be seen from the head of the department trying to appreciate the potential of each employee, decisions are always formulated together, leaders do not limit the creativity of subordinates and provide opportunities to subordinates to work and develop; 3) the head of the department always tries to encourage community participation in infrastructure development.